STRATEGI PDIP DALAM ONE ISLAND ONE MANAGEMENT UNTUK PEMENANGAN PILGUB BALI TAHUN 2018 - Pontoh, Cinthia; Bandiyah, Bandiyah; Jayanthi, AA Sagung Mirah Mahaswari (Jurnal Nawala Politika; 2019, 2019)
ABSTRACT PDIP is a party with a long history in Indonesia especially in Bali, but the depreciation in PDIP's performance in Bali in the past few years questioning the existence of PDIP in Bali. To  maintaining the existence of the party, PDIP comes with one of its strategies, One Island One Management. This study uses a qualitative method, where interviews, documentation and literature is uses as the data collection techniques. Sampling  using purposive sampling technique, with respondents are Koster-Ace campaign team from PDIP.The results of the study suggest that PDIP uses the One Island One Management political strategy which then correlates with the mapping strategy in the form of mapping the political power of PDIP in Bali as a winning strategy where this strategy brings PDIP to victory in the governor election and wins 57.68% of the votes. One Island One Management is one of the important aspects for PDIP as a goal of building a more prosperous Bali while gaining a dominating mass base by making Bali management and governance managed by PDIP both from the regions and at the center, namely Governor. In order to realize this idea PDIP carried out a mapping strategy that was used so that it succeeded in transforming the masses into voices and pairs carried out by PDIP namely Koster-Ace won the Bali Pilgub in 2018 . Keywords: Pilgub, PDIP, Strategi Politik, One Island One Management.